Battling Resistance to Antibiotics and Pesticides : an Economic Approach. - Laxminarayan, Ramanan (Earthscan, 2002)
The increasing resistance of bacteria to antibiotics, and pests to pesticides, threatens to undo some of the most remarkable advances made in public health and agriculture during the past century. Though the potential consequences of increased antibiotic and pesticide resistance are far reaching, regulatory efforts to address the problem are at a very early stage. Battling Resistance to Antibiotics and Pesticides moves such discussions forward by presenting cutting edge research and the first comprehensive application of economic tools to analyze how antibiotics and pesticides should be used t.